2011
DOI: 10.1152/jn.01049.2010
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted stepping modulates monosynaptic reflexes in forearm muscles in the human

Abstract: Nakajima T, Kitamura T, Kamibayashi K, Komiyama T, Zehr EP, Hundza SR, Nakazawa K. Robotic-assisted stepping modulates monosynaptic reflexes in forearm muscles in the human.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 35 publications
6
46
1
Order By: Relevance
“…The subjects were instructed to relax, and not to intervene with the movements imposed by the DGO during the passive stepping, and practiced the passive stepping task for a few minute before recording. To examine the effect of velocity, passive stepping was performed at five different stride frequencies (14,21,28,35, and 42 min −1 ). Stride frequency (min −1 ) was defined as the number of strides per minute.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects were instructed to relax, and not to intervene with the movements imposed by the DGO during the passive stepping, and practiced the passive stepping task for a few minute before recording. To examine the effect of velocity, passive stepping was performed at five different stride frequencies (14,21,28,35, and 42 min −1 ). Stride frequency (min −1 ) was defined as the number of strides per minute.…”
Section: Methodsmentioning
confidence: 99%
“…It would be better that the effect of afferent input on the ol H-reflex during walking is studied in passive movements more similar to "natural" walking. Recently, a passive stepping paradigm with a driven-gait orthosis (DGO; Lokomat ® , Hocoma AG, Switzerland) has been used to investigate the effects of afferent input on H-reflex excitability during walking [9,14]. As DGO can support the upright posture of the subjects and impose passive stepping movements that are much similar to "walking," it is useful to elucidate the effects of afferent input during walking without any influence from descending inputs from the higher nervous centers.…”
Section: Introductionmentioning
confidence: 99%
“…In recently, our group revealed that stepping-related afferent feedback suppressed the excitability of H-reflex pathway for forearm muscle [6]. This study *Resrach supported by KAKENHI: Grant-in-Aid for Scientific Research (B) 21300202.…”
Section: Introductionmentioning
confidence: 76%
“…Expansion of cortical excitatory area and change of representation was often reported after motor skill learning with improving motor performance [13]. Moreover in previous report which investigate leg or arm H-reflex during remote extremity movement [6][11] [14], it was revealed that excitability of H-reflex pathway is suppressed. This inhibition is thought to be due to presynaptic inhibition facilitated by lower limb movement [11] [14].…”
Section: Functional Implicationmentioning
confidence: 99%
“…Also, reflex modulation in the legs during combined rhythmic arm and leg movement is sensitive to contributions from the arms [8] and there is specific tuning of this coupling at the level of the motoneuronal pool [9]. There is also a strong reciprocal organization such that rhythmic leg movement modulates cervical spinal cord excitability [10][11][12][13][14].…”
Section: Persistent Somatosensory and Locomotor-activated Linkages Bementioning
confidence: 99%